Relações étnico-raciais: uma análise dos aspectos interseccionais na assistência em transplantes de órgãos e tecidos - Silva, Brena Miranda da (2023)
Tracing a correlation between the health of the black population and organ and tissue transplantation has become a challenge, since studies in the area are scarce, and the consulted literature showed that the main factors that affect the performance of transplants are in addition to biological causes (age, ethnicity, compatibility/blood type and time on dialysis) there are aspects linked to ethnic and racial relationships that imply graft survival. Thus, in this qualitatively eminence study, I propose to discuss the health of the black population and the intersections of race/color in the organ transplant service, aiming to understand how the expressions of racial inequalities and their intersectionalities impact the health-care process. disease among users of the organ and tissue transplantation service treated at the Renal and Liver Transplant Outpatient Clinic of the Walter Cantídio University Hospital (HUWC). As well as, to describe the trajectory of access to the organ and tissue transplant service during the pandemic proliferated by the COVID-19 Virus, to elaborate a socio-racial profile of the users of the organ/tissue transplant service, and, finally, to analyze the intersections of race/color in accessing and/or staying in the transplant service. Regarding the methodological aspects, I will use the following research techniques: simple observation, semi-structured interview and document analysis. In the course of the study, I have the following objectives that guided this research: To this end, I will follow as a theoretical basis the following scholars on the subject of ethnic-racial relations, collective health and human rights, such as: Guimarães (2005), Munanga (2006), Schwarcz ( 1998), Werneck (2007), Almeida (2019) and Mbaya (1997). In short, it was inferred that there are disparities in the access to the transplant service, with the black population being the target of institutional racism that structurally operates in the capitalist social formation and strategically functions as a defining mechanism of social places. In short, the old inequalities arising from the slave colonial period are re-edited and have resulted in profound violations of human rights, which tear and weaken population minorities.